Analisis Setting Novel Laksamana Malahayati Sang Perempuan Keumala Karya Endang Moerdopo - Nurliza, Eli; Nurul Azmi; Ismawirna; Faisal; Junaidi; Asriani (Kodepena Indonesia, 2024)
Analisis latar dalam novel